“O estádio me espera, vai começar a festa”: o espetáculo promovido pela Equipe Vai Rolar a Festa e a Equipe de Bateria da TOC nos estádios cearenses no período pós-copa de 2014 - Silva, Ingryd Melyna Dantas da (2020)
Through this research we intend to understand the social effects of the Sports Mega Events Confederations Cup 2013 and World Cup 2014, as well as the transformations carried out at Castelão Stadium, and comprehend in what way they have contributed to changes in the dynamics of the fans who operate in the city of Fortaleza/CE, especially fans linked to Ceará Sporting Club. For that, we have outlined the following specific goals: present normalizations thought for the World Cup 2014, especially through the General Law of the Cup and the Code of Conduct in the Stadiums continued to be applied in the Ceará Sporting Club soccer stadiums even after the end of the Sports Mega Events; specify how the new normalizations applied in the Ceará Sporting Club soccer stadiums, especially in Castelão Stadium, intervened in the performance of the Ceará Sporting Club fans; and describe which elements compose the performance of the Ceará Sporting Club fans nowadays. To better analyze the object, we use the qualitative approach, and as for procedures, we adopt bibliographic, documentary and field research. Regarding the field research, we accompanied the Cearamor Organized Crowd Drums Team and the Vai Rolar a Festa Team in the spaces where their activities were carried out, especially in Plácido Aderaldo Castelo Stadium, the Castelão. Through the research, we could see that the Brazilian stadiums have undergone intense transformations over the years and that these transformations have caused refractions for fans and supporters. In addition, we identified three stadium construction cycles in the country. The third and final cycle began when Brazil was chosen to host the World Cup 2014. On that occasion, twelve stadiums were built or refurbished to meet FIFA's requirements. Among them, the Castelão Stadium in Fortaleza. From the fan reports, it is possible to infer that, after the remodeling of Castelão Stadium into an Arena and after the World Cup 2014, the mechanisms of surveillance and control of fans have increased, as well as the bans, especially on the instruments that make up the fan performance. This occurred because part of the guidelines that were passed on by FIFA to be applied during the Mega Events continued to be used in Brazilian stadiums even after the World Cup. Therefore, we believe that the World Cup 2014 has had an impact on fan practices and has changed the dynamics of Brazilian fans and fans. One of the impacts observed was the replacement of instruments to perform the fan performance and the expansion of the party held in the stands. Presently, these parties resemble huge concerts, as they need several people involved in the elaboration and assembly stages; as well as good amounts of money and preparation time. In addition, it was possible to see the shows promoted by the Organized Supporters and the Party Teams gain other contours when they are performed on Clássico-Rei days, because the show itself becomes an element of dispute. Thus, the Organized Supporters and the Party Teams dedicate days of preparation to ensure victory in the stands and hope that their team wins on the field.